2017
DOI: 10.1038/s41598-017-09472-y
|View full text |Cite
|
Sign up to set email alerts
|

Diversification dynamics of rhynchostomatian ciliates: the impact of seven intrinsic traits on speciation and extinction in a microbial group

Abstract: Ciliates are a suitable microbial model to investigate trait-dependent diversification because of their comparatively complex morphology and high diversity. We examined the impact of seven intrinsic traits on speciation, extinction, and net-diversification of rhynchostomatians, a group of comparatively large, predatory ciliates with proboscis carrying a dorsal brush (sensoric structure) and toxicysts (organelles used to kill the prey). Bayesian estimates under the binary-state speciation and extinction model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Nevertheless, Bayesian diversification analyses favors a birth‐death model over a pure‐birth model both in the metopid‐clevelandellid group (present study) and in rhynchostomatians (Vďačný et al. ), suggesting attrition of some lineages via extinction. Diversification patterns of spathidiid ciliates might be, however, comparatively different from those of metopids, clevelandellids, pleurostomes and rhynchostomatians.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Nevertheless, Bayesian diversification analyses favors a birth‐death model over a pure‐birth model both in the metopid‐clevelandellid group (present study) and in rhynchostomatians (Vďačný et al. ), suggesting attrition of some lineages via extinction. Diversification patterns of spathidiid ciliates might be, however, comparatively different from those of metopids, clevelandellids, pleurostomes and rhynchostomatians.…”
Section: Discussionmentioning
confidence: 49%
“…Diversification dynamics is only rarely examined in ciliates due to the lack of fossil records (Rajter and Vďačný ; Vďačný ; Vďačný et al. ; Wright and Lynn ). However, this problem could be overcome by the fossil appearance of hosts of the exclusively endosymbiotic clevelandellids, whose origin cannot precede that of their host groups.…”
mentioning
confidence: 99%
“…Rhynchostomatia was established by Jankowski (1980) as one of three subclasses of the class Litostomatea. This subclass comprises two orders, Tracheliida and Dileptida ( Vd’ačný et al, 2017 ). Phylogenetic analyses based on 18S, 5.8S, and ITS rDNA sequence data demonstrated that each of these two orders is monophyletic ( Figures 6A , 7 , 8 ), which is consistent with previous studies ( Vd’ačný et al, 2011b , 2014 ; Jang et al, 2014 ; Vd’ačný and Rajter, 2015 ; Huang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rhynchostomatians are raptorial feeders whose predatory lifestyle has led to the development of special structures for prey recognition and capture. The primary feature is the apical proboscis which carries a dorsal brush that may be used for sensory feedback, extrusomes (toxicysts) to paralyze and/or kill prey organisms, and differentiated kineties such as the circumoral kinety (∼paroral membrane) and preoral kineties (∼adoral zone of membranelles) to aid feeding ( Visscher, 1923 ; Dragesco, 1962 ; Vd’ačný and Foissner, 2012 ; Vd’ačný et al, 2017 ; Chi et al, 2021 ). Furthermore, differences in hunting strategies and preferred prey among dileptids ( Vd’ačný and Foissner, 2012 ) seem to be related to these differentiated structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation